(untitled) (Research, Society and Development, 2023)
Music therapy is the use of music and/or elements (sound, rhythm, melody and harmony), in a group or individually, in a process to facilitate and promote communication, relationship, learning, mobilization, expression, organization and other therapeutic objects relevant, in the sense of meeting physical, emotional, mental, social and cognitive needs. the study aims to identify the benefits of using music therapy as a therapeutic tool in the health area. This is an integrative literature review, which searches were carried out in the LILACS, SciELO and MEDLINE databases, resulting in 193 articles that, after reading, 15 articles were selected to compose the final sample. Studies report that music therapy has positive effects in palliative care, bringing about a decrease in pain, blood pressure levels, respiratory and heart rate, anxiety, and also a decrease in depressive symptoms and the consumption of anxiolytics, as well as a feeling of freedom, good memories of home and their families. In this way, music therapy can be an effective non-pharmacological intervention to assist in clinical treatment in the future that is increasingly widespread and used, not only for patients in palliative care, with cancer and other diseases that involve hospitalization, but with any other state of illness to relieve symptoms.